Role of Macrophages in Early Host Resistance to Respiratory Acinetobacter baumannii Infection - Qiu, Hongyu; KuoLee, Rhonda; Harris, Greg; Van Rooijen, Nico; Patel, Girishchandra B.; Chen, Wangxue (PLOS ONE, 2012)
Acinetobacter baumannii is an emerging bacterial pathogen that causes nosocomial pneumonia and other infections. Although it is recognized as an increasing threat to immunocompromised patients, the mechanism of host defense against A. baumannii infection remains poorly understood. In this study, we examined the potential role of macrophages in host defense against A. baumannii infection using in vitro macrophage culture and the mouse model of intranasal (i.n.) infection. Large numbers of A. baumannii were taken up by alveolar macrophages in vivo as early as 4 h after i.n. inoculation. By 24 h, the infection induced significant recruitment and activation (enhanced expression of CD80, CD86 and MHC-II) of macrophages into bronchoalveolar spaces. In vitro cell culture studies showed that A. baumannii were phagocytosed by J774A.1 (J774) macrophage-like cells within 10 minutes of co-incubation, and this uptake was microfilament- and microtubule-dependent. Moreover, the viability of phagocytosed bacteria dropped significantly between 24 and 48 h after co-incubation. Infection of J774 cells by A. baumannii resulted in the production of large amounts of proinflammatory cytokines and chemokines, and moderate amounts of nitric oxide (NO). Prior treatment of J774 cells with NO inhibitors significantly suppressed their bactericidal efficacy (P<0.05). Most importantly, in vivo depletion of alveolar macrophages significantly enhanced the susceptibility of mice to i.n. A. baumannii challenge (P<0.01). These results indicate that macrophages may play an important role in early host defense against A. baumannii infection through the efficient phagocytosis and killing of A. baumannii to limit initial pathogen replication and the secretion of proinflammatory cytokines and chemokines for the rapid recruitment of other innate immune cells such as neutrophils.